Molecular and Metabolic Markers of Fructose Induced Hepatic Insulin Resistance in Developing and Adult Rats are Distinct and Aegle marmelos is an Effective Modulator. Issue 1 (December 2018) - Nair, Jayachandran; Velpandian, Thirumurthy; Das, Ujjalkumar; Sharma, Prateek; Nag, Tapas; Mathur, Sandeep; Mathur, Rajani
Abstract The time course of pathogenesis of fructose mediated hepatic insulin resistance (HepIR) is not well-delineated and we chronicle it here from post-weaning to adulthood stages. Weaned rats were provided for either 4 or 8 weeks, i.e., upto adolescence or adulthood, chow + drinking water, chow + fructose, 15% or chow + fructose, 15% + hydroalcoholic extract of leaves ofAegle marmelos (AM-HM, 500 mg/kg/d, po) and assessed for feed intake, fructose intake, body weight, fasting blood sugar, oral glucose tolerance test, HOMA-IR, insulin tolerance test and lipid profile. Activities of enzymes (glucose-6-phosphatase, hexokinase, phosphofructokinase, aldehyde dehydrogenase), hormones (leptin, ghrelin, insulin), insulin signaling molecules (Akt-PI3k, AMPK, JNK) hallmarks of inflammation (TNF-α), angiogenesis (VEGF), hypoxia (HIF-1), lipogenesis (mTOR) and regulatory nuclear transcription factors ofde novo lipogenesis and hepatic insulin resistance gene (SREBP-1, FoxO1) that together govern the hepatic fructose metabolism, were also studied. The effect of fructose-rich environment on metabolic milieu of hepatocytes was confirmed using (human hepatocellular carcinoma) HepG2 cells. Usingin vitro model, fructose uptake and glucose output from isolated murine hepatocytes were measured to establish the HepIR under fructose environment and delineate the effect of AM-HM. The leaves from the plantAegle marmelos (L) Correa were extracted, fractionated and validated for rutin content using LC-MS/MS. The rutin content of extract was quantified and correlated with oral pharmacokinetic parameters in rat. The outcomes of the study suggest that the molecular and metabolic markers of fructose induced HepIR in developing and adult rats are distinct. Further, AM-HM exerts a multi-pronged attack by raising insulin secretion, augmenting insulin action, improving downstream signaling of insulin, reducing overall requirement of insulin and modulating hepatic expression of glucose transporter (Glut2). The butanol fraction of AM-HM holds promise for future development.